Lactobacillus casei UT1 Isolated from Northwest of Iran Traditional Curd Exerts Anti-proliferative and Apoptosis Inducing Effects in Human Colorectal Tumor HCT 116 Cells - Mitra Rabiei; Gholamreza Zarrini; Majid Mahdavi (Tabriz University of Medical Sciences, 2020)
Purpose: The present study was mainly designed to assess anti-cancer effects of lactobacilli isolated from traditional dairy products, on HCT116 colorectal cancer cell lines. Methods: Traditional dairy products samples were collected from the region of Azarbayjan and the suspensions were cultured in MRS agar medium. The isolates were identified by biochemical and molecular methods. Isolated bacteria were cultured in MRS broth. Supernatants of the isolates cultures were collected and their cytotoxicity was evaluated on HCT116 cancer cells. Morphological changes of the treated cells by supernatant were observed using an inverted microscope. Cell metabolic activity was assessed by MTT assay. The morphology of apoptotic cells was examined using a fluorescent microscope. In cell cycle analysis, content measurement of DNA was performed by flow cytometry. Results: Out of 30 lactobacilli were isolated from dairy products samples, six isolates belong to curd samples. Cell-based assays showed that culture supernatant of one isolate (UT1) had a significant anticancer effect on colorectal HCT116 cell lines (P<0.05). The 16S rRNA sequence analysis revealed that the isolate UT1 was 99% compatible with Lactobacillus casei. Conclusion: It is noteworthy that the supernatant of L. casei UT1 can be candidate for studies on compounds having anti-cancer effect.